Monetary Value of Live Trade in a Commonly Traded Primate, the Long-Tailed Macaque, Based on Global Trade Statistics - Hansen, Malene Friis; Gill, Mike; Briefer, Elodie Floriane; Nielsen, Daniel R. K.; Nijman, Vincent (Frontiers in Conservation Science, 2022)
Non-human primates (primates) are regarded as key research subjects for pre-clinical trials of several drugs aimed to alleviate human suffering. It has long been suggested that the predominant species in the international trade in live primates for use in research is the long-tailed macaque (Macaca fascicularis). However, little is still known about the value of this international trade. Whilst the international trade to supply the requirement for biomedical testing is known to encourage illegal wildlife trade, we lack a detailed understanding of the overall value and magnitude of this trade. Such information is vital to facilitate the design of effective conservation strategies in range countries, in order to mitigate the exploitation of wild populations by organized crime networks. Here, data from CITES and the UN Comtrade databases were combined to calculate the value of this trade. We also compared the number of individual primates traded as reported in the two databases to investigate possible correlations. Results show that, from 2010 to 2019, the international trade in long-tailed macaques constituted a market worth of ~US $1.25 billion. We found a positive correlation between individual primates traded in the UN Comtrade Database and individual long-tailed macaques reported in the CITES Trade Database, suggesting that we can use the UN Comtrade database to investigate values and magnitude of the international legal trade in wildlife, and that legal trade in live primates is primarily constituted of long-tailed macaques alone.